(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Ethnomedicinal study on Butea monosperma (Lam.) Taub. revealed that native people of Netrokona district extensively use flower, bark and leaves of the plant to treat different kinds of diseases. People of the studied area used the plant to treat goiter, diabetes, painful menstruation, body swellings, intestinal worms, urinary stone, leucorrhoea and chronic fever. Application of root powder mixed with honey as an antidote for snake bite was recorded for the first time. Phytochemical screening of the methanolic extracts of flowers, leaves and stem of this plant showed the presence of carbohydrate, flavonoid, glycosides, saponins, terpenoids and steroids. Through qualitative assessment, flower was found to be rich in flavonoids compared to leaf and stem. Leaf extract of B. monosperma showed relatively higher cytotoxicity than flower and stem extracts. The highest free radical scavenging activity was observed in flower sample (73.49%) and the lowest in leaf sample (48.17%). The results of the present study may be a proof of a scientific basis for the use of B. monosperma in traditional medicine. Jahangirnagar University J. Biol. Sci. 4(2): 19-29, 2015 (December)